2019
DOI: 10.1097/corr.0000000000000803
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Association Between Prophylactic Femur Stabilization and Survival in Patients with Metastatic Bone Disease?

Abstract: Background The femur is the most common site of metastasis in the appendicular skeleton, and metastatic bone disease negatively influences quality of life. Orthopaedic surgeons are often faced with deciding whether to prophylactically stabilize an impending fracture, and it is unclear if prophylactic fixation increases the likelihood of survival. Questions/purposes Is prophylactic femur stabilization in patients with metastatic disease associated with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 37 publications
1
28
0
1
Order By: Relevance
“… 18 , 19 Prophylactically stabilizing a metastatic lesion (compared with the fixation of a completed pathological fracture) is cost-effective, lessens the burden on the healthcare system, and is associated with an improvement in overall survival. 4 , 20 , 21 Furthermore, these surgeries tend to be less morbid with shorter hospital stays and higher likelihood of discharge to home rather than a facility.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 , 19 Prophylactically stabilizing a metastatic lesion (compared with the fixation of a completed pathological fracture) is cost-effective, lessens the burden on the healthcare system, and is associated with an improvement in overall survival. 4 , 20 , 21 Furthermore, these surgeries tend to be less morbid with shorter hospital stays and higher likelihood of discharge to home rather than a facility.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“… 1 - 3 Metastatic lesions put patients at risk for pathological fracture, leading to substantial morbidity associated with hospital admission, pain, worsening quality of life, and perhaps decreased overall survival. 4 The femur is the most common site of metastatic disease and pathologic fracture in the appendicular skeleton. 5 …”
mentioning
confidence: 99%
“…In the study by Phillipp et al, for example, we expect their estimates of survival are probably overestimates. 17 …”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 However, most studies on metastatic bone disease are small, single-center studies 12 13 14 15 16 or use larger databases with limitations that stem from retrospective design, low granularity, and lack of statistical control. 17 Some studies have used the CPT and ICD codes to define cohorts of patients with metastatic disease of the femur, 17 whereas others do not explicitly state the criteria or methodology that were used to identify patient cohorts. 12 13 14 15 16 , 18 - 20 Efforts to produce studies with larger sample sizes will likely rely on structured data to identify patient cohorts.…”
mentioning
confidence: 99%
“…Philipp et al found that patients with femoral metastases who underwent prophylactic internal fixation had a lower mortality rate than patients treated for pathologic femur fractures ( p = 0.002) [ 60 ]. El Abiad et al reinforced this data and reported that prophylactic fixation was related to a lower risk of complications ( p = 0.02) and shorter hospital stay ( p = 0.01) than post-fracture stabilization [ 61 ].…”
Section: Main Textmentioning
confidence: 99%